Isolation of MERS-related coronavirus from lesser bamboo bats that uses DPP4 and infects human-DPP4-transgenic mice - Susanna K. P. Lau (Nature Portfolio, 2021)
Several human coronaviruses (CoV) have been proposed to emerge from bats but evidence of direct bat-to-human transmission is slim. In this work, the authors isolate a MERS-related CoV strain directly from bats and show that it infects target cells in vitro and engineered mice through the human DDP4 receptor.